The effect of cardiolipin synthase deficiency on the mitochondrial function and barrier properties of human cerebral capillary endothelial cells - Nguyen, Hieu Thi Minh (Elsevier, 2015)
The blood brain barrier (BBB), formed by endothelial cells lining the lumen of the brain capillaries, is a restrictively permeable interface that only allows transport of specific compounds into the brain. Cardiolipin (CL) is a mitochondrial- specific phospholipid known to be required for the activity and integrity of the respiratory chain. The current study examined the role of cardiolipin in maintaining an optimal mitochondrial function that may be necessary to support the barrier properties of the brain microvessel endothelial cells (BMECs). Endothelial cells have been suggested to obtain most of their energy through an-aerobic glycolysis based on studies of cells that were obtained from the peripheral vasculatures. However, here, we showed that the adult human brain capillary endothelial cell line (hCMEC/D3) appeared to produce ~60% of their basal ATP requirement through mitochondrial oxidative phosphorylation. In addition, RNAi mediated knockdown of the CL biosynthetic enzyme cardiolipin synthase (CLS), although did not grossly affect the mitochondrial coupling efficiency of the hCMEC/D3 cells, did seem to reduce their ability to increase their mitochondrial function under conditions of increased demand. Furthermore, the knockdown appeared to have acted as a metabolic switch causing the hCMEC/D3 cells to become more dependent on glycolysis. These cells also showed increase in [3H]-2-deoxyglucose uptake under a low glucose availability condition, which might have served as a mechanism to compensate for their reduced energy production efficiency. Interestingly, the increase in glucose uptake appeared correlated to an increase in [3H]-2-deoxyglucose glucose transport across the knockdown confluent hCMEC/D3 monolayers grown on Transwell® plates, which was used in our study as an in vitro model for the human BBB. This suggests that changes in the brain endothelial energy status may play a role in regulating glucose transport across the BBB. These observations, perhaps, also explain why the brain capillary endothelial cells were previously observed to possess higher mitochondrial content than those coming from non-BBB regions (Oldendorf et al. 1977).